Plastic ingestion by Scyliorhinus canicula trawl captured in the North Sea. (May 2018) - Smith, L.E.
Abstract: The ingestion of plastic debris by marine organisms has been documented across a variety of taxa including; marine mammals, sea birds, sea turtles and some fish species. Fewer reports have described ingestion by sharks, in this study the gastrointestinal tracts of 20 small spotted catsharks ( Scyliorhinus canicula ) trawl captured in the North Sea were investigated. Macroplastics (>20 mm) were found in 2 individuals and microplastic (<5 mm) was found in one other individual, this is the first time that plastic ingestion has been reported in this species. These observations suggest that gastrointestinal analysis of commonly landed elasmobranch species is worthwhile, to further understanding on the organisms and habitats impacted by plastic pollution. Highlights: Macroplastics and microplastic were found in the stomach contents of 3 Scyliorhinus canicula This is the first time plastic ingestion has been reported in Scyliorhinus canicula This is important due to human consumption of larger individuals of this species and thus potential toxin ingestion.